(untitled) (The Peerian Journal, 2022)
This article scientifically analyzes the principle of "Respect for human rights in the New Uzbekistan" based on the reforms adopted at the initiative of President Shavkat Mirziyoyev. The practical significance of the concept of human rights in the process of formation of democratic values, civil society and free market relations in our country is revealed.